2020
DOI: 10.1108/jefas-07-2017-0081
|View full text |Cite
|
Sign up to set email alerts
|

Loss aversion, overconfidence of investors and their impact on market performance evidence from the US stock markets

Abstract: Purpose-The current study aims to investigate the impacts of two behavioral biases, namely, loss aversion and overconfidence on the performance of US companies. First, the impact of loss aversion on the economic performance of companies was assessed. Second, the impact of overconfidence on market performance was discussed. Design/methodology/approach-This study used around 6,777 quarterly observations on the population of US-insured industrial and services companies over the 2006-2016 period. Ordinary least sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 84 publications
3
57
0
Order By: Relevance
“…Figure 2: Structural ModelResults for loss aversion and regret aversion emotional biases had similarities with past researches like(Hoffmann, Post, et al 2015),(Bouteska and Regaieg 2018),(Shah and Malik 2021), (Awais and Estes 2019), and (Lee and Veld-Merkoulova 2016). Whereas, risk perception results were contrary to past literature available both in the case of PSX and other developing stock markets e.g., results of (Khan 2016, Khan 2017),(Shehata, Abdeljawad, et al 2021), and(Shafi, Hussain, et al 2011) showed that risk perception harms investment trading but this study reflects it has an insignificant and positive impact on the trading frequency of individual investors while investing in PSX.…”
supporting
confidence: 81%
“…Figure 2: Structural ModelResults for loss aversion and regret aversion emotional biases had similarities with past researches like(Hoffmann, Post, et al 2015),(Bouteska and Regaieg 2018),(Shah and Malik 2021), (Awais and Estes 2019), and (Lee and Veld-Merkoulova 2016). Whereas, risk perception results were contrary to past literature available both in the case of PSX and other developing stock markets e.g., results of (Khan 2016, Khan 2017),(Shehata, Abdeljawad, et al 2021), and(Shafi, Hussain, et al 2011) showed that risk perception harms investment trading but this study reflects it has an insignificant and positive impact on the trading frequency of individual investors while investing in PSX.…”
supporting
confidence: 81%
“…As It is believed that the weight of loss surpasses the weight of the gain, indicating that psychological loss is more painful than the psychological gain of equivalent value. In this line, Individual investor under loss aversion uses profits in decision rather loss in order to avoid the emotional and psychological pains and regret Tversky,1979 Shiller, 1998).As such individual investors assume or feel that if loss is not realised for investment in the financial market , then profits will be earned on investment (Bouteska and Regaieg, 2018).With this mind the investor wants to obtain profits from the investment by quickly selling good assets to avoid decrease in stock price but maintain and refuse to trade non performing security below the purchase price. Considering the fact that loss is a classic example of regret of aversion, there is the possibility that investors will feel the pains of regret for loss of investment and wish to avoid such pains of regrets (Shiller, 1998).…”
Section: Loss Aversion (Prospect Theory)mentioning
confidence: 99%
“…This subjective decision can expose managers to several biases, including loss aversion (Tversky and Kahneman, 1974) which is one of less studied managerial biases compared to overconfident bias. Following the theoretical evidence of Tversky and Kahneman (1974), much of the literature in loss aversion comes from investors (Rephael et al 2012;Bouteska andRegaieg, 2018 andfund managers (Bodnarruk, 2016) show that loss aversion bias highly influence financial decisions. However, there is still limited knowledge about loss aversion behaviors of managers(owners) of SMEs, given their managerial role and as key financier.…”
Section: Introductionmentioning
confidence: 99%
“…Overconfidence is overestimation or under estimation. It generally occur when public information is ignored and priority or emphasis is given to investor's own knowledge and wisdom [10]. Media response bias: This bias checks the influence of media reporting on the investment decision made by the investors.…”
Section: Literature On Behavioural Biasesmentioning
confidence: 99%